PE_PGRS38 Interaction With HAUSP Downregulates Antimycobacterial Host Defense via TRAF6 - Kim, Jae-Sung; Kim, Hyo Keun; Cho, Euni; Mun, Seok-Jun; Jang, Sein; Jang, Jichan; Yang, Chul-Su (Frontiers in Immunology, 2022)
Mycobacterium tuberculosis (Mtb) is the causative pathogen of tuberculosis (TB), and intracellular infection is followed by host-pathogen interaction to ensure successful survival and colonization in the host. Mtb possess a unique family of proteins, named PE_PGRS, associated with Mtb pathogenesis. Thus, elucidation of the functions of PE_PGRS proteins is necessary to understand TB pathogenesis. Here, we investigated the role of PE_PGRS38 binding to herpesvirus-associated ubiquitin-specific protease (HAUSP, USP7) in regulating the activity of various substrate proteins by modulating their state of ubiquitination. We constructed the recombinant PE_PGRS38 expressed in M. smegmatis (Ms_PE_PGRS38) to investigate the role of PE_PGRS38. We found that Ms_PE_PGRS38 regulated the cytokine levels in murine bone marrow-derived macrophages by inhibiting the deubiquitination of tumor necrosis factor receptor-associated factor (TRAF) 6 by HAUSP. Furthermore, the PE domain in PE_PGRS38 was identified as essential for mediating TRAF6 deubiquitination. Ms_PE_PGRS38 increased the intracellular burden of bacteria by manipulating cytokine levels in vitro and in vivo. Overall, we revealed that the interplay between HAUSP and PE_PGRS38 mediated the inflammatory response, which is vital for the intracellular survival of mycobacteria.